Rapid Assessment Framework : An Innovative Decision Support Tool for Evaluating Energy Efficiency Opportunities in Cities - World Bank (Washington, DC, 2014)
The Rapid Assessment Framework (RAF) is a central component of the Energy Efficient Cities Initiative (EECI), launched by the Energy Sector Management Assistance Program (ESMAP) in collaboration with the urban Anchor in 2008. The World Bank's key objective for the RAF is to create: 'a practical tool for conducting rapid assessment in cities to identify and prioritize sectors and suggest specific energy efficiency interventions.' Thus, the RAF will be used to help identify areas of energy use for further focus, develop an outline energy efficiency strategy, and guide potential future investment by ESMAP. The principal aim of the RAF is to provide a practical analytical framework for conducting rapid assessment of a developing country city's energy profile and performance for different activities across different sectors. This information is then used to identify sectors where the most improvements can be made, and provide a range of energy efficiency recommendation options for each sector, along with a list of possible actions. An outline energy efficiency strategy should ultimately be generated from this information to guide potential policy and investment options, helping the city to save energy and money. The sectors include transport, buildings, water/waste water, public lighting, solid waste, and power/heating. The organizational management practices of the City Authority (CA) that span all of the sectors are also considered to capture cross-sector integration and achieve an overall efficiency in the urban system.